Influence of polarization coulomb field scattering on the subthreshold swing in E-mode p-GaN/AlGaN/GaN HEMTs - Heyu Liu; Mingyan Wang; Heng Zhou; Guohao Yu; Honghuan Guo; Baoshun Zhang; Peng Cui; Zhaojun Lin (Journal of Physics Communications)
In the present study, p-GaN/AlGaN/GaN HEMTs treated with hydrogen plasma passivation were fabricated. Capacitance–voltage (C-V) and current–voltage(I-V) characteristics of these devices were subsequently measured. The relationship between polarization Coulomb field (PCF) scattering and the subthreshold swing(SS) for E-mode p-GaN/AlGaN/GaN was investigated. The two-dimensional electron gas (2DEG) concentration beneath the gate-source (G-S) and gate-drain (G-D) regions of the p-GaN HEMT was calculated at zero gate bias voltage using TCAD software. By integrating measured I-V and C-V data, the 2DEG concentration was determined for various gate bias voltages, facilitating iterative calculations to derive additional parameters such as polarization charge and electron mobility. The calculation results show that for the E-mode GaN HEMT, the PCF was gradually weakened as the additional polarization charge decreased with the increase in V _GS . Moreover, for the devices with stronger PCF scattering, the value of the SS was smaller, and the SS value was reduced by over 60%.